2011
DOI: 10.1039/c0cc05208f
|View full text |Cite
|
Sign up to set email alerts
|

One of the most complex “small molecule structures” ever reported: 16 independent molecules in the asymmetric unit for an ortho-palladated primary amine

Abstract: The presumably "small molecule structure" of the organopalladium complex rac-PdCl(C(6)H(3)-4-OMe-CHMeNH(2))(py) crystallizes with 16 molecules in the asymmetric unit, a highly unusual situation according to the CSD database. The symmetrically independent residues differ with respect to soft conformational degrees of freedom. Packing in the acetonitrile solvate of the same compound is unexceptional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This hypothesis seem at odds with the observation that both independent molecules in the asymmetric unit have very similar folded conformations. The apparent differences between independent molecules are not over interpreted as being different conformers as in the case of others high Z' structures [44,45]. The observation of very similar conformations in the structure of cis-1,2,3,6-tetrahydropthalic anhydride (Form I) and its second polymorph (Form II) may be interpreted to mean that differences between formula groups are consequence rather than a cause of high Z' behaviour.…”
Section: Results Of Theoretical Calculations and Comparison With Expementioning
confidence: 97%
“…This hypothesis seem at odds with the observation that both independent molecules in the asymmetric unit have very similar folded conformations. The apparent differences between independent molecules are not over interpreted as being different conformers as in the case of others high Z' structures [44,45]. The observation of very similar conformations in the structure of cis-1,2,3,6-tetrahydropthalic anhydride (Form I) and its second polymorph (Form II) may be interpreted to mean that differences between formula groups are consequence rather than a cause of high Z' behaviour.…”
Section: Results Of Theoretical Calculations and Comparison With Expementioning
confidence: 97%
“…Studies have shown that where a large number of solid-state structures exist, the conformations obtained correlated to the energetic minima in a fluxional system, 36,37 and that in general the conformational variation displayed across a number of structures of the same compound provides a good estimation of its flexibility in solution. 38 The relatively low diversity of conformations of 1 exhibited here can therefore be taken to give a representative sample of those displayed in solution.…”
Section: Dimerisation In Solutionmentioning
confidence: 99%
“…In previous work by Calmuschi & Englert, all intermediates along the reaction pathway used to synthesize (I) (see Scheme) have been structurally characterized (Calmuschi & Englert, 2002;Calmuschi, Jonas & Englert, 2004). A variety of pyridine derivatives have been used successfully as -donor ligands (Calmuschi, Alesi & Englert, 2004;Calmuschi-Cula et al, 2005, 2006, 2009Braun et al, 2011). In the present case, we intended to introduce the electronically similar ligand quinoline as an approximate steric equivalent to the nucleobase guanine; guanine itself is only sparingly soluble in solvents compatible with the organopalladium starting material.…”
mentioning
confidence: 99%